Source Note: The Textual Record of Climate Change at Sea. Issue 4 (22nd August 2020) - Degroot, Dagomar
Abstract: Anthropogenic climate change is today transforming Earth's oceans with alarming speed, imperiling the fate of all of us on land. Preindustrial and overwhelmingly natural climate changes were, in the Holocene, far smaller in scale and speed than those of today. Yet they too reshaped the oceans and thereby powerfully influenced historical societies. This short essay aims to inspire a new wave of scholarship on the social impacts of past climate change at sea by introducing environmental historians to the rich and still largely underexploited treasure trove of sources that make such work possible. It describes these sources and their relative merits; explains how they can be used to identify, or "reconstruct, " periods of past climate change; and shows how they may be used to reveal human responses to those changes. It devotes special attention to the preindustrial period, for which scholarship is especially scant, and to textual evidence from archives in Europe and North America, which is plentiful as early as the seventeenth century. Uniquely, it shows how these sources may be used to write environmental histories of the oceans.